Drug addiction: targeting dynamic neuroimmune receptor interactions as a potential therapeutic strategy. (February 2016) - Jacobsen, Jonathan Henry W; Hutchinson, Mark R; Mustafa, Sanam
Highlights: Drugs of abuse activate the neuroimmune system. The neuroimmune system is pivotal to the progression of addiction. Multiple independent parallel systems are not sufficient to explain complex states. Integrated signalling networks are crucial for addictive behaviours. Targeting receptor interactions may offer a novel therapeutic intervention. Abstract : Drug addiction and dependence have proven to be difficult psychiatric disorders to treat. The limited efficacy of neuronally acting medications, such as acamprosate and naltrexone, highlights the need to identify novel targets. Recent research has underscored the importance of the neuroimmune system in many behavioural manifestations of drug addiction. In this review, we propose that our appreciation for complex phenotypes such as drug addiction and dependence will come with a greater understanding that these disorders are the result of intricate, interconnected signalling pathways that are, if only partially, determined at the receptor level. The idea of receptor heteromerisation and receptor mosaics will be introduced to explain cross talk between the receptors and signalling molecules implicated in neuroimmune signalling pathways.